The Influence of Safety Leadership and Work Engagement on Job Satisfaction - Ahmad Fadli (Yayasan Bina Bisnis Nusantara Medan, 2024)
This study aims to analyze the effect of safety leadership and work engagement on job satisfaction among employees at Mahkota Tricom Superior University. While work engagement reflects the emotional and cognitive involvement of employees in the work of lecturers, safety leadership emphasizes the importance of work safety. This study employs a quantitative approach and a survey method, with 35 permanent lecturers serving as respondents. We analyzed the data using multiple linear regression to determine the impact of each independent variable on the dependent variable. The results showed that safety leadership has a positive and significant effect on job satisfaction, indicating that leadership that focuses on work safety can increase employee satisfaction. Additionally, the results demonstrated a positive and significant impact of work engagement on job satisfaction, suggesting that employee involvement in lecturers' work directly influences the level of lecturer satisfaction. The combination of safety leadership and work engagement simultaneously makes a significant contribution to increasing job satisfaction. This study offers practical recommendations for university management to prioritize enhancing safety-based leadership and bolstering employee engagement in their efforts to boost job satisfaction